Life, Death & Magic : 2000 Years of Southeast Asian Ancestral Art - Maxwell, Robyn (Canberra National Gallery of Australia, 2010)
Provides an evocative overview of the region's ancestral arts and culture, from prehistoric times to the twenty first century. Prolifically illustrated with works of art drawn from museums around the world and the National Gallery of Australia's exceptional collection of Southeast Asian art.
Include Color Illustration, Acknowledgment and Bibliography
Keywords: Art -- Symbolism in art -- Southeast Asian